Analysis of rainfall-induced landslide on unsaturated soil slopes - Jeong, Sangseom (2018)
This paper investigates rainfall-induced landslides on partially saturated soil slopes using the 2011 Umyeonsan landslides at the center of Seoul, Korea. An integrated analysis of rainfall-induced landslide was carried out through laboratory tests, field tests, and numerical analysis. The results of comprehensive investigations in the Umyeonsan region demonstrate that landslide activity is closely related primarily to rainfall and soil properties and slope geometry, and vegetation. Numerical analysis was also performed to confirm the effect of these factors on landslide occurrence. Special attention was given to rainfall penetration analysis to determine the wetting band depth for shallow and deep-seated slope failure in watershed-scale landslide. The simulated results agree closely with the investigation results, which indicates that the applied method is appropriate for use in the simulation of landslides in unsaturated soils.